(untitled) (Al-Qamar, 2022)
Mir Dard was a famous Sufi poet of Urdu Literature in eighteenth Century Although his poetry stands in a shorter single Urdu Dewan but enough for his reliable repute in Urdu poetic history. His valuable poetry not only Attracts so many historians, authors and a lot of readers but they also quoted it a lot- Thats why khairati Lāl Bē Jigar also amused by his poetry and gave him a special place in his “Memorandum of Urdu Poets”. The importance of this memorandum is that the compiler has represented rare and collective information about Urdu Poets which other history books did not have. Moreover, this poetic collection has rare autobiographical information about rare poets that why is very helpful for researchers. In the case of Mir Dard, he placed about eleven pages for his biography and selected poetry- Major part of this memorandum is still unpublished. This article is an effort to produce, compare and edit rare information about Mir Dard for researchers and scholars.